The Development of an Affective Assessment Instrument Based on Creativity and Critical Thinking on Reaction Rate Material - Yessi Prihartina; Das Salirawati (Jurnal Tadris Kimiya, 2023)
This study aims to determine the characteristics of the assessment instrument, feasibility, and description of the affective aspects of students in the reaction rate material. The measure affective aspects are creativity and critical thinking attitudes. The research method is research and development (R&D) developed with a 4-D model. The research subject was taken from second-grade Senior High School with a random sampling technique. The initial product of the instrument was content validated by expert judgment, which was calculated using the Aiken formula and construct validity using Confirmatory Factor Analysis. The results showed that the instrument was declared feasible based on the content validity of 0.976 with a good category. The construct validity results stated that 18 fit items from 21 statement items. The description of the affective aspects of students in the reaction rate material from 213 students showed that the average student is in a good category.